Feasibility of reducing differences in estimated doses in nuclear medicine between a patient-specific and a reference phantom. (July 2017) - Zvereva, Alexandra; Schlattl, Helmut; Zankl, Maria; Becker, Janine; Petoussi-Henss, Nina; Yeom, Yeon Soo; Kim, Chan Hyeong; Hoeschen, Christoph; Parodi, Katia
Highlights: Individual patient anatomy limits accuracy of dose estimates in nuclear medicine. Polygon-mesh ICRP adult male model scaled to fit selected dimensions of patients. Matched models provided reliable dose estimates for overweight and slim patients. Estimation of individual patient doses within relative uncertainty ≤25% possible. Detailed segmentation of patient not required for personalised internal dosimetry. Abstract: The feasibility of reducing the differences between patient-specific internal doses and doses estimated using reference phantoms was evaluated. Relatively simple adjustments to a polygon-surface ICRP adult male reference phantom were applied to fit selected individual dimensions using the software Rhinoceros®4.0. We tested this approach on two patient-specific phantoms: the biggest and the smallest phantoms from the Helmholtz Zentrum München library. These phantoms have unrelated anatomy and large differences in body-mass-index. Three models approximating each patient's anatomy were considered: the voxel and the polygon-surface ICRP adult male reference phantoms and the adjusted polygon-surface reference phantom. The Specific Absorbed Fractions (SAFs) for internal photon and electron sources were calculated with the Monte Carlo code EGSnrc. Employing the time-integrated activity coefficients of a radiopharmaceutical (S)-4-(3- 18 F-fluoropropyl)-l -glutamic acid and the calculated SAFs, organ absorbed-dose coefficients were computed following the formalism promulgated by the Committee on Medical Internal Radiation Dose. We compared the absorbed-dose coefficients between each patient-specific phantom and other models considered with emphasis on the cross-fire component. The corresponding differences for most organs were notably lower for the adjusted reference models compared to the case when reference models were employed. Overall, the proposed approach provided reliable dose estimates for both tested patient-specific models despite the pronounced differences in their anatomy. To capture the full range of inter-individual anatomic variability more patient-specific phantoms are required. The results of this test study suggest a feasibility of estimating patient-specific doses within a relative uncertainty of 25% or less using adjusted reference models, when only simple phantom scaling is applied.